Between Ethics, Digitalization, and Gender: The Dynamics of Tax Evasion among Non-Employee WPOPs in DIY - Azmi, Muhammad Tsabitul; Sri Lestari Yuli Prastyatini (E-Jurnal Akuntansi, 2025)
This study examines the influence of moral obligations and the use of information technology on the intention to evade taxes among non-employee individual taxpayers in the Special Region of Yogyakarta, taking into account the role of gender as a moderating variable. Data were obtained by distributing questionnaires to 109 randomly selected respondents. The analysis results indicate that moral obligations and the use of information technology have a negative effect on the tendency to engage in tax evasion. Gender was found to moderate this relationship, where the influence of moral obligations on tax evasion is strengthened by gender, while the influence of information technology on tax evasion is weakened when moderated by gender. These findings emphasize the importance of strengthening moral values and optimizing information technology in efforts to curb tax evasion practices, while taking into account gender differences.